The Relationship between Length of Work and Educational Level of Anesthetists on the Level of Knowledge About Non-Pharmacological Therapy in Treating Post-Spinal Anesthesia Hypotension - Parwati, Putu Atika; Arta, Sang Ketut; Wahyuningsih, Luh Gde Nita Sri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pharmacological therapy in treating hypotension after spinal anesthesia causes various side effects including tachycardia, headache, edema, body electrolyte imbalance, acid base imbalance, volume overload, anaphylaxis and coagulopathy. Non-pharmacological therapy can be an alternative choice to avoid the side effects of pharmacological therapy. Knowledge is one of the things needed in implementing non-pharmacological therapy. Knowledge is influenced by several factors, including education level and length of work. Through this research, we want to know the relationship between length of work and level of education with the level of knowledge of non-pharmacological therapy. The research design used is correlation analytical research with a cross-sectional approach. The population taken were anesthetists in Bali using a total sampling technique. The sample in this study was 102 anesthetists using a total sampling technique. Bivariate analysis with the chi square test was carried out to test the relationship between length of work and level of education with the level of knowledge of non-pharmacological techniques in treating hypotension. The results of the study concluded that the level of knowledge had a significant relationship with length of work (p < 0.001) and level of education (p < 0.001).